2011
DOI: 10.1111/j.1939-1676.2011.0678.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cisplatin as an Electrochemotherapy Agent for the Treatment of Incompletely Excised Mast Cell Tumors in Dogs

Abstract: Background: Electrochemotherapy (ECT) couples the administration of anticancer drugs with the delivery of electric pulses that increase the drug uptake through the cell membranes, resulting in an improved efficacy.Hypothesis: To evaluate the tolerability and efficacy of cisplatin (CDDP) as an ECT agent to prevent recurrence of incompletely resected mast cell tumors (MCTs).Animals: Thirty-seven dogs. Methods: Prospective study recruiting dogs with incompletely excised MCTs as confirmed by surgeon and pathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 8 publications
1
56
0
6
Order By: Relevance
“…As opposed to highly-toxic chemotherapy and radiation therapy regimes, all EBTs are well-tolerated by patients due to a lack of post-procedural complications [5,6]. Because the mechanism of cell death does not rely on thermal processes, outcomes are not subject to heat sink effects from blood perfusion, which can protect tumors from thermal therapies.…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to highly-toxic chemotherapy and radiation therapy regimes, all EBTs are well-tolerated by patients due to a lack of post-procedural complications [5,6]. Because the mechanism of cell death does not rely on thermal processes, outcomes are not subject to heat sink effects from blood perfusion, which can protect tumors from thermal therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Solid tumors of various etiologies are being treated successfully. In veterinary medicine several studies have already demonstrated the effectiveness, convenience and safety of ECT with either cisplatin or bleomycin for the treatment of spontaneous tumors, such as soft-tissue sarcomas in cats, mast cell tumors and perianal tumors in dogs and sarcoids in horses [8][9][10][11][12][13][14]. In clinical settings ECT is currently used with palliative intent for the treatment of predominantly melanoma cutaneous metastases, as well as in head and neck tumors, basal cell carcinomas, and adenocarcinomas in humans [15][16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…The healing of sutured wound edges in the partially resected tumour site without any complications such as wound dehiscence indicated that the settings for the delivery of square wave electric pulses of 100 microseconds, at 1300V/cm, with a frequency of 500Hz was safe and had anti-tumour effect along with cisplatin (Spugnini et al, 2006) without tissue damage and thermal injury. Additionally application of electrical pulses injured the vascular endothelial cells of the tissues surrounding tumours, thus decreasing the flow of blood (vascular lock) resulting in cyto-reduction and tumour cell apoptosis (Bass et al,2017).…”
Section: Resultsmentioning
confidence: 99%
“…Square wave electric pulses of 100 microseconds, at 1300V/cm, with a frequency of 500Hz was delivered through two parallel stainless steel electrodes attached to therapeutic electroporator machine ( ELECTROvet S13, LEROY Biotech, France). Each run of electric pulses was delivered in 2 trains of 4 pulses, with 1-second interval in first series and the second series was delivered perpendicular to the first direction of electrode placement or in a hexagonal pattern (Spugnini et al, 2006). Good contact between the electrodes and the skin was assured by depilation and application of a conductive gel to the treatment area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation